Tribological investigation of tetrahedral diamond-like carbon (ta-C DLC) coatings using vegetable oil containing anti-wear additives / Abdul Mannan - Abdul, Mannan (2018)
Friction and wear are considered as the nuance for machineries and need to reduce as much as possible. Use of proper lubricants and the treatment of interfacial surfaces can be a way of reducing both friction and wear. This study is about the tribological performance of tetrahedral diamond-like carbon (ta-C DLC) coating where the investigations were performed in Steel/Steel, Steel/DLC and DLC/DLC contacts in the presence of canola oil with and/or without additives. The Steel/Steel contact was investigated as the reference contact. The results varied between contacts and oils such as the coefficient of friction (COF) in Steel/Steel, Steel/DLC and DLC/DLC contacts under base oil was 0.062, 0.059 and 0.048, and under additivated oil was 0.066, 0.067 and 0.058 respectively. Both oils showed lowest wear in Steel/Steel contact and the Steel/DLC and DLC/DLC contact showed approximately 76% and 8% higher wear than Steel/Steel contact respectively when tested with base oil. The wear reduced in all contacts under additivated oil and this was higher in metal containing contacts such as approximately 79% in Steel/Steel, 66% in Steel/DLC and 60% in DLC/DLC contact. The wear reduction by additives might be due to the chemical absorption with steel and physical absorption with DLC surface as DLCs are known as “non-reactive”. The agglomeration of transferred particles in Steel/DLC under base oil was not found when tested with additivated oil. The damage of coating in DLC/DLC was not present when tested with additivated oil. Therefore, it can be said that the tribological properties can be improved applying DLC coating and further improvement can be done by additivating the base oils.